1993
DOI: 10.1021/ma00073a032
|View full text |Cite
|
Sign up to set email alerts
|

Radical ring-opening polymerization of .alpha.-cyclopropylstyrenes. Polymerization behavior and mechanistic aspects of polymerization by the molecular orbital method

Abstract: Synthesis and radical polymerization of substituted a-cyclopropylstyrenes [l-(4-substituted phenyl)-1-cyclopropylethylene; 3a (X = OMe), 3b (X = H), and 3c (X = Cl)] were carried out. 3a-c were prepared by the Wittig reaction of the corresponding cyclopropyl aryl ketones. The radical polymerization of 3 was performed in the presence of an appropriate radical initiator (3 mol % vs monomer) at 60-120 O C . The molecular weight of the polymer obtained decreased while the conversion of the monomer increased, as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…1,2-Propanedithiol (9) was synthesized by modifying the procedure reported by Culvenor and Davies. 29 Propylene oxide was reacted with carbon disulfide in sodium hydroxide in methanol to give the propylene trithiocarbonate (10). Instead of using alcoholic potassium hydroxide to hydrolyze the trithiocarbonate, ethanolamine was added directly to the neat trithiocarbonate and the liberated dithiol (9) was distilled directly from the reaction in over twice the yield reported for the hydroxide method (64 vs 26%).…”
Section: Monomers and Their Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…1,2-Propanedithiol (9) was synthesized by modifying the procedure reported by Culvenor and Davies. 29 Propylene oxide was reacted with carbon disulfide in sodium hydroxide in methanol to give the propylene trithiocarbonate (10). Instead of using alcoholic potassium hydroxide to hydrolyze the trithiocarbonate, ethanolamine was added directly to the neat trithiocarbonate and the liberated dithiol (9) was distilled directly from the reaction in over twice the yield reported for the hydroxide method (64 vs 26%).…”
Section: Monomers and Their Synthesismentioning
confidence: 99%
“…Over the last 20 years, free radical ring-opening polymerization has been seen as a solution to the problem of polymerization volume shrinkage. Reports, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] patents, [15][16][17][18] and reviews 19,20,21 in this field appear regularly in the literature, and a monograph 22 also has been published. Whereas much work continues on ketene acetal 23 and vinylcyclopropane derivatives, 24 we have developed novel cyclic allylic sulfide monomers such as the activated monomer 1 5,15,25 and the unactivated monomers 2-4.…”
Section: Introductionmentioning
confidence: 99%
“…The cyclobutane formation is considered a possible reason for the large volume shrinkage. To reduce the generation of recyclization units, a bulky substituent, such as a phenyl group on a cyclopropane ring, can be used . Sugiyama et al reported that introducing the bulky phenoxycarbonyl or adamantyloxycarbonyl group reduced the cyclobutane unit formation, and the 1,5‐ring‐opened reaction proceeded quantitatively on to RROP, where the volume expansion (4%–6%) was successfully achieved .…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] However, the vinylcyclopropane RROP causes a volume shrinkage (11%-17%), which is greater than that of a common cyclic monomer. [6][7][8][9][10] The detailed investigation of the polymer structure revealed that the polymer is involved, not only in the proposed 1,5-adduct unit but also in cyclobutane unit, which is formed via backbiting of the propagating radical to a double bond of the main chain. 8 The cyclobutane formation is considered a possible reason for the large volume shrinkage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation